Longitudinal Evidence for a Midlife Nadir in Human Well-being: Results from Four Data Sets - Terence Chai Cheng; Nattavudh Powdthavee; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2014)
There is a large amount of cross-sectional evidence for a midlife low in the life cycle of human happiness and well-being (a 'U shape'). Yet no genuinely longitudinal inquiry has uncovered evidence for a U-shaped pattern. Thus some researchers believe the U is a statistical artefact. We re-examine this fundamental cross-disciplinary question. We suggest a new test. Drawing on four data sets, and only within-person changes in well-being, we document powerful support for a U-shape in unadjusted longitudinal data without the need for regression equations. The paper's methodological contribution is to exploit the first-derivative properties of a well-being equation.
Keywords: I31; D01; C18; 330; life-cycle happiness; subjective well-being; longitudinal study; U shape